(untitled) (World Bulletin of Social Sciences, 2024)
In the rapidly evolving landscape of education, the role of technology in enhancing teaching practices has become increasingly significant. One key aspect of this transformation is the empowerment of teachers through the use of digital resources and platforms. By integrating these tools into their teaching methodologies, educators can not only streamline administrative tasks but also personalize learning experiences for students. This article explores the concept of enhancing teacher autonomy with digital resources and platforms, highlighting the benefits, challenges, and implications of this innovative approach